Preparation of Pore-Size Controllable Activated Carbon from Rice Husk Using Dual Activating Agent and Its Application in Supercapacitor - Khu Le Van; Thuy Luong Thi Thu (Journal of Chemistry)
Activated carbons prepared from rice husk by chemical activation with dual activation agents, KOH and NaOH, have been studied and characterized by BET, SEM, EDX, FTIR, Boehm titration, Raman, and TGA. It was found that the KOH/NaOH impregnation ratio plays an important role on textural properties of AC. At the same amount of total alkali hydroxide, the KOH/NaOH ratio higher than 1.33 resulted in larger specific surface area (2990∼3043 m2·g−1), microporous surface area (2747∼2831 m2·g−1), and higher micropore volume (1.4250∼1.4316 cm3·g−1). The as-prepared samples exist in the form of spherical-shaped particles with the size ranging from 20 to 60 nm and contain numerous surface functional groups. The as-prepared activated carbons were then assessed as an electrode material of supercapacitor operating in the 0.5 M K2SO4 electrolyte in potential windows of −1.0∼0.0 V. The highest capacitance obtained was 205 F·g−1 at the scan rate of 2 mV·s−1 and 225 F·g−1 at a current density of 0.2 A·g−1. At the scan rate as high as 50 mV·s−1, all the as-prepared activated carbons in this study have the specific capacitance greater than 100 F·g−1.